An attractive approaches in studying basic oc (organic chemistry) - Me, Ropisah; Hasan, Nur Syakilla Asyiqin; Hasan, Nur Syaida Maisarah (Universiti Teknologi MARA, Kedah, 2023)
Traditional ways of learning have indirectly affected students' creativity in memorizing and understanding a topic of basic organic chemistry. This time-honored of learning needs to be changed in the hope of keeping the interest of students in learning more complex subjects like organic chemistry. Basic organic chemistry is a study of structure, properties, and reactions of organiccompounds that consist of carbon-hydrogen bond or carbon-carbon bond within their structures. It is important to learn about basic organic chemistry because it is a study of life since every matter thatwe use in our daily life is composed of organic compounds. Therefore, understanding organic chemistry is crucial and various approaches can be taken to engage society to enjoy learning organic chemistry since organic chemistry is a killer subject. In this study, several attractive approaches have been discussed to develop creativity and interest in learning organic chemistry. The mind mapping concept is one of the methods that helps students to organize their thoughts and has shown the ease of remembering ideas. Alternatively, online learning platforms such quizzes and kahoot is anotherattractive way to enhance learning activity. These approaches are as boosters that must try to enjoy learning organic chemistry and perhaps can easily understand it.